KEKERASAN DALAM RUMAH TANGGA AKIBAT DARI KURANGNYA PEMAHAMAN TERHADAP AGAMA, HILANGNYA AKHLAQUL KARIMAH DAN LEMAHNYA KOMUNIKASI PADA KELUARGA SERTA RASA EGOISME YANG BERLEBIHAN - Mudemar A. Rasyidi (JURNAL MITRA MANAJEMEN, 2016)
Abstract Violence in household is occurred due to lack of understanding on religion, loss goodcharacter and weak communication in family as well as excessive egoism, lack ofunderstanding on the meaning of marriage, lack of faith and no obedience to Allah(God) the Creator of the Universe, not willing to accept fate and too love of the world(materials). In addition, since human being (people) do not respect each other, as theconsequence human being (people) have lost guidance and do know direction in theirlives.Keywords: Family Law No. 23 of 2004 and Child Protection Law No. 23 of 2002,Domestic Violence Law, Domestic Violence Resolution (Domestic Violence)at Religious Court, Marriage Law in Indonesia, Holy Qur’an and Hadits, andother sources.